Next-generation sequencing-based small RNA profiling of cerebrospinal fluid exosomes. (1st January 2017) - Yagi, Yohsuke; Ohkubo, Takuya; Kawaji, Hideya; Machida, Akira; Miyata, Haruka; Goda, Saori; Roy, Sugata; Hayashizaki, Yoshihide; Suzuki, Harukazu; Yokota, Takanori
Highlights: This study used NGS to analyse CSF and serum exosomal fractions. Exosomal miRNA profiles differed between CSF and serum. miR-1911-5p was specific for CSF exosomes. Our results have important implications for the origin of CSF exosomal miRNAs. Abstract: MicroRNAs (miRNAs), particularly those found in human body fluids, have been suggested as potential biomarkers. Among various body fluids, the cerebrospinal fluid (CSF) shows promise as a profiling target for diagnosis and monitoring of neurological diseases. However, relevant genome-scale studies are limited and no studies have profiled exosomal miRNAs in CSF. Therefore, we conducted a next-generation sequencing-based genome-wide survey of small RNAs in the exosomal and non-exosomal (supernatant) fractions of healthy human CSF as well as serum in each donor. We observed miRNA enrichment in the exosomal fractions relative to the supernatant fractions of both CSF and serum. We also observed substantial differences in exosomal miRNA profiles between CSF and serum. Half of the reported brain miRNAs were found in CSF exosomal fractions. In particular, miR-1911-5p, specifically expressed in brain tissue, was detected in CSF but not in serum, as confirmed by digital PCR in three additional donors. Our data suggest that the brain is a major source of CSF exosomal miRNAs. Here we provide the important evidence that exosomal miRNAs in CSF may reflect brain pathophysiology.